Graphene nanoribbon antenna modeling based on MoM-GEC method for electromagnetic nanocommunications in the terahertz range. Issue 8 (23rd May 2016) - Aidi, M.; Hajji, M.; Ben Ammar, A.; Aguili, T.
Abstract: In this paper, we present a graphene nanoribbon (GNR)-based terahertz antenna array modeling using the MoM-GEC method (the moments method combined with the generalized equivalent circuit). The quantum mechanical conductivity of graphene is used to introduce the graphene's effect in the mathematical formulation. The GNR is excited by a gap source with unit voltage localized in its center. The antenna structure is shielded in a rectangular waveguide with electric boundary walls. The proposed formulation is firstly validated and it yields efficient and accurate solutions. The obtained input impedance, current density distribution, and radiated electric field are presented to discuss the antenna performance in cases of single and antennas array. It is demonstrated that all results verify the boundary conditions and behave correctly corresponding to the physical laws. Furthermore, we showed that the antenna array leads to enhance the far-field communications for lower distances compared to conventional antenna.